Reflorestamento ciliar do Ribeirão Pira no Povoado Passarinho Município de Tocantinópolis: um estudo da prática transdisciplinar no processo de ensino-aprendizagem dos alunos do 4° ano „d‟ da Escola Municipal Alto da Boa Vista - Souza, Elia Gomes de (Universidade Federal do Tocantins, 2022)
This intervention project has as main objective to apply the practice of reforestation with the students of the Municipal School Alto da Boa Vista II, to then contribute to the recovery of the degraded areas of the Pira Stream, which is located on TO-210 in the town birdie , in the municipality de Tocantinópolis -TO. The methodology used is that of exploratory and qualitative research initiated with a bibliographic survey. The data collected in the elaboration of the referred project inform us of the importance of the process of sustainable learning of the environment, as a way to foster in the collective student and teacher, actions that concretize the doing and acting on the environment respecting the nature, in order to find objectives proposed to work on transdisciplinary practice in favor of the environment in the school context. It seeks to provide readers with a contextualization from which perspective the research was designed and executed. And so, making it possible to show in this project how important reforestation is for education and for the community. With this work it will be possible to develop theory and practice from the perspective of creative praxis with students within the school context, thus seeking to form engaged subjects who adopt environmental education in their daily lives, that is, in their home or community so that this knowledge does not remain at school only.